2015
DOI: 10.1159/000437145
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Vertical Hemispherotomy: A Single Center Experience

Abstract: Purpose: Hemispheric epileptogenic lesions such as hemimegalencephaly often manifest as intractable epilepsy in early infancy. Hemispherotomy is the treatment of choice for controlling intractable hemispheric epilepsy. Less invasive procedures are desirable for surgery on infants with low body weight. This study compared our experience with interhemispheric vertical hemispherotomy (IVH) and peri-insular lateral hemispherotomy (PIH). Methods: Thirteen consecutive patients underwent hemispherotomy for treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Our findings contrast two studies directly comparing vertical and lateral techniques, which found favorable outcomes overall but no differences between groups. One of these studies was underpowered to detect differences in seizure outcome, 24 whereas the other was a national multicenter study comprising 90 patients across three main Italian epilepsy centers with a methodology similar to ours. 20 Our calculated rates of seizure freedom at the last follow‐up for vertical (86.1%) and lateral (79.0%) approaches were almost identical to the latter study, which had 84.2% and 73.1% seizure freedom in the vertical and lateral groups, respectively; however, the utilization of a modified interhemispheric approach by de Palma et al yielded a much lower rate of seizure freedom for their vertical group overall and may explain the different conclusions between our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings contrast two studies directly comparing vertical and lateral techniques, which found favorable outcomes overall but no differences between groups. One of these studies was underpowered to detect differences in seizure outcome, 24 whereas the other was a national multicenter study comprising 90 patients across three main Italian epilepsy centers with a methodology similar to ours. 20 Our calculated rates of seizure freedom at the last follow‐up for vertical (86.1%) and lateral (79.0%) approaches were almost identical to the latter study, which had 84.2% and 73.1% seizure freedom in the vertical and lateral groups, respectively; however, the utilization of a modified interhemispheric approach by de Palma et al yielded a much lower rate of seizure freedom for their vertical group overall and may explain the different conclusions between our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative blood transfusion and the total duration of surgery have been shown to be less in vertical hemispherotomy. 24 Increased blood loss in lateral hemispherotomy is thought to be associated with the greater amount of tissue resected, with the exception of the keyhole technique. 19 The risk of hydrocephalus is thought to be higher in lateral hemispherotomy due to resection of the subarachnoid space of the Sylvian fissure, although the 2%–20% rate of hydrocephalus in lateral series 16 , 17 , 19 , 38 , 39 appears to be comparable with 3%–16% in vertical series.…”
Section: Discussionmentioning
confidence: 99%
“…33 We used a stringent definition of seizure freedom, which required studies using the Engel classification to report Engel Ia. However, if we had considered Engel I as seizure freedom, seizure freedom in Pinto et al 33 would increase to 66% (10 of 15); also, 4 other studies 19,22,25,31 reporting rates of 55%-81% (consistent with the range of seizure freedom rates we already identified) would have been included.…”
Section: Hemispherectomy/hemispherotomymentioning
confidence: 99%
“…Favorable outcome after epilepsy surgery could depend on multiple factors, including underlying etiology. Eight studies 21,22,24,26,31,32,34 for HME, 92% (12/13) for FCD/MCD without HME, and 93% (13/14) for other pathology.…”
Section: Hemispherectomy/hemispherotomymentioning
confidence: 99%
“…7,8 VPH was later introduced according to the method of Delalande et al 9,10 A technical modification was made as reported elsewhere and was applied in some patients. 11 Posterior quadrantectomy was performed in patients with a posterior quadrantic epileptogenic lesion. The technical details are as previously reported.…”
Section: Surgerymentioning
confidence: 99%